Search 82,173 tutors
FIND TUTORS

Arthur D.'s Resources

Answers

(-8a^3b)^(1/3) is the numerator -8 is -2 cubed take out -2 and a from the radicand leaving b inside (-2a)*(3√b) is the numerator (27b^10)^(1/3) is the denominator 27 is 3 cubed and b^10=b^9*b take out 3 and b^3 from the radicand leaving b inside (3*3*3=27 and b3*b3*b3=b9) 3b3*(3√b)...

Answers

distance=rate*time total distance=rate*total time You can't add the two rates and divide by two because the time going and the time coming back are different. The distance does not matter because it is the same coming and going. Because the distance does not matter, we can use an...

Answers
solve problem (answer)

115.3º go counterclockwise 360º and then go counterclockwise 115.3º to get 115.3+360=475.3º add another 360º to get 360+475.3=835.3º go clockwise 360-115.3=244.7º to get -244.7º go clockwise another 360 to get -360+(-244.7)=-604.7º

Answers

distance=rate*time d=r*(2.7) for Eugene d=(r+16.1)*2 for Jose 2.7r=2(r+16.1) 2.7r=2r+32.2 0.7r=32.2 7r=322 r=46 km per hour for Eugene r+16.1=46+16.1=62.1 km per hour for Jose

Answers
word problems (answer)

m=mother's age s=son's age m=s2 m-1=7(s-1) substitute s2-1=7(s-1) s2-1=7s-7 s2-1-7s+7=0 s2-7s+6=0 factor (s-6)(s-1)=0 s-6=0 s=6 m=62=36 the mother is 36 and the son is 6 one year ago their ages were 35 and 5 and 35 is 7*5

Answers

2^(1-x)=8^(3x+1) 8=2^3 2^(1-x)=(2^3)^(3x+1) 2^(1-x)=2^(3*(3x+1)) 2^(1-x)=2^(9x+3) since the bases are the same the exponents are equal to each other (1-x)=(9x+3) 1-x=9x+3 1=9x+x+3) 1=10x+3 1-3=10x -2=10x x=-2/10 x=(-1/5)...

Answers

Here's another solution. I think the amount of each solution is missing. 7:3 means 7/10=70% milk 3:2 means 3/5=60% milk assume each solution is 100 liters 70%(x)+60%(100-x)=66 2/3%(100) because 2:1 means 2/3=66 2/3 % milk 0.7x+0.6(100-x)=66 2/3 0.7x+60-0.6x=66...

Answers

(1/2)/8=(1/2)*(1/8)=1/16 received by each think of it this way... if you had a whole cake each person would get 1/8 of the cake, but you only have half of a cake so everybody gets 1/2 of what they would have gotten so each person gets 1/2 of 1/8 which is 1/16

Answers

[(x/4)-(4/x)]/[1-(4/x)] [(x^2-16)/4x]/[(x-4)/x] [(x-4)(x+4)/4x]*[x/(x-4) simplify (x+4)/4   (x^(-2)-y^(-2))/(x^(-1)) (x^(-2))/(x^(-1))-(y^(-2)/x^(-1)) x/(x^2)-x/(y^2) (1/x)-(x/y^2), or if you want a single fraction... (y^2-x^2)/xy^2

1 2 3 4 5